Parliamentary Representation in Six European Right-Wing Sovereignist Parties: Resemblance or Innovation?. Issue 3 (2nd April 2021) - Borri, Rossella; Verzichelli, Luca
Abstract: The appeal to the re-appropriation of national sovereignty has recently become the unifying trait of a heterogeneous group of right-wing parties. The underlying reasoning behind this claim is that globalised elites ignore the needs of the people—defined as a restricted and ethnically homogeneous group of natives—they are supposed to represent. After defining the perimeter of this party cluster, including populist, national conservatives and extreme-right parties, this article explores the extent to which the adoption of similar political platforms might also be reflected in a convergence of parliamentary party articulations. A qualitative account of the evolution of parliamentary representation in a few right-wing parties from Italy, Hungary and the Netherlands shows that a two-way street of institutionalisation might be at play in the complex balance between uncompromising grassroots components and a more pragmatic institutional component.